Isoliensinine Prevents against Lipopolysaccharide-induced Rat Acute Lung Injury and Sepsis via Inhibiting the Inflammatory Mediators - Gao, Lili; Qi, Jie (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Novel pharmaceuticals have been largely derived from natural substances. Through this experimental study, we sought to assess the impacts of Isoliensinine (ILS) on Acute Lung Injury (ALI) and sepsis caused by Lipopolysaccharide (LPS) in rats. Materials and Methods The rats were assigned to 3 different groups: control, LPS-induced and LPS+ILS. ILS exhibits a wet/dry weight ratio was measured. Blood Serum AST, ALT, ALP and hsCRP levels were measured. Also, levels of oxidative stress markers such as SOD, CAT, GPx and MDA were also analysed. ELISA was used to assess the quantities of inflammatory cytokine TNF-α, IL-1β, IL-6 and IL-10 and using a light microscope histopathological changes were examined. Results ILS treatment dramatically enhanced lung tissue architecture while decreasing wet/dry weight ratio. It significantly inhibited the pro-inflammatory cytokine cascade. Group III (LPS+ILS) exhibited lower levels of ALT, AST, ALP and hsCRP. It has antioxidant properties by boosting the levels of SOD, CAT and GPx while decreasing MDA concentration. Conclusion ILS has significant protective properties against LPS-induced lung damage as it lessens LPS-induced indications of lung injury while suppressing pro-inflammatory and oxidative stress markers. Thus, ILS could be a potential treatment for clinical ALI and sepsis. During the study, nurses emphasized the importance of monitoring vital signs, providing oxygen therapy, ensuring animal health, conducting ethical research and collecting accurate data for future research on ILS, which may have a potential for human use.
Keywords: Isoliensinine; Acute Lung Injury; Sepsis; Anti-Inflammatory; Lipopolysaccharide.